Optimization of Coca-Cola Product Distribution Routes at PT. Graha Prima Mentari Medan With Ant Colony Optimization - Tarigan, Pridolin Olin; Mansyur, Abil (UIN Sumatera Utara, 2021)
PT Graha Prima Mentari is a company engaged in the service sector, namely as the official distributor of Coca-Cola. PT. Graha Prima Mentari has Distribution Centers spread across various cities including those located in the cities of Cirebon, Indramayu, Tasikmalaya, Pekanbaru, Medan, Denpasar, Rembang and others. For branches in the city of Medan PT. Graha Prima Mentari is located at Jalan Gatot Subroto KM 6.7 No. 100 Fields. PT. Graha Prima Mentari has 13 transportation cars that operate from Monday to Saturday and serve 6 areas, namely Medan Barat, Medan Sunggal, Medan Helvetia, Medan Selayang, Medan Tuntungan and Medan Petisah.The problem that occurs is that the company has not determined the optimal route which results in additional costs for the distribution of goods. This study aims to minimize the distance by using the ant colony optimization method. The result obtained is that the distribution distance is reduced by 52 km from the previous distance of 93.1 km to 41.1 km and saves distribution costs of Rp.49,000.